Promosi Coffee Tubruk Bamboo - Fajri Muhammad; San Ahdi (Jurnal Kajian dan Penelitian Umum, 2023)
Coffee Tubruk Bamboo is a coffee brand in the city of Padang owned by Rizky Afrizal Candra. Coffee currently lacks a distinctive identity, therefore a new identity is created in the form of a logo. This logo incorporates colors and typography that encapsulate the original concept, aiming to make it memorable for both current and potential customers. The logo draws inspiration from the shape of a bamboo plant and coffee beans, symbolizing the signature of a business run from a bamboo-themed setting and complemented by the presence of coffee beans, all accompanied by a lettermark of the name “Coffee Tubruk Bamboo. " The design is in harmony with modern aesthetics while maintaining a playful shape. To develop a promotion strategy for Coffee Tubruk Bamboo, an analysis using the framework "5W+1H" (what, who, where, when, why, and how) is used. This approach aims to reveal solutions and overcoming challenges. The design process begins with observations and interviews with the owner of Coffee Tubruk Bamboo, ensuring the collection of important data for promotion strategies. Main promotional media includes posters, along with supporting materials such as packaging, X-banner displays, business cards, tote bags, stickers , promotional videos, and screen printing t-shirts.